COMPARISON OF INTRATHECAL HYPERBARIC ROPIVACAINE 0.5% WITH AND WITHOUT 75 MG MAGNESIUM SULFATE AS AN ADJUVANT FOR INFRA UMBILICAL SURGERIES: A DOUBLE-BLIND RANDOMIZED CLINICAL TRIAL - SRIKANTH, SRINIDHI; CHARLES S, ANTONY JOHN; KAMESHWAR YV; MISHRA, GAYATRI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Intrathecal magnesium as an adjuvant to hyperbaric ropivacaine could extend duration of sensory blockade and improve the quality of post-operative analgesia; thereby reducing opioid requirements and its adverse effects. Hence, we conducted this prospective, randomized, double-blind clinical trial to observe its effects for day care surgeries. Methods: After obtaining institutional ethical committee approval and registration of trial, patients’ informed consent was taken and eighty adult patients of either gender, ASA 1 and 2, posted for infra umbilical surgeries were divided into two groups: Group RM received 3 ml hyperbaric Ropivacaine with 0.75 ml magnesium sulfate (75 mg) and Group R received 3 ml hyperbaric Ropivacaine with 0.75 ml sterile water. Sensory and motor blockade parameters, hemodynamic variables, and adverse effects were monitored, analyzed using appropriate statistical tests. Results: Total duration of sensory blockade was significantly prolonged in Group RM compared to Group R (242.8 ± 9.9 versus 186.6 ± 8.4 min) (***p<0.001). Complete motor regression was observed significantly earlier in Group RM than in Group R (151.3 ± 7.8 versus 184.7 ± 5.6 min) (*p<0.05). Post-operative pain free interval was significantly prolonged in group RM compared to group R (725.2 ± 18.6 vs. 515.2 ± 17.8 min) (***p<0.001). Conclusion: We concluded that intrathecal magnesium as an adjuvant to hyperbaric Ropivacaine significantly prolonged both sensory blockade duration, post-operative pain-free interval without increasing motor blockade duration and the incidence of adverse effects.